A Call-To-Action: Integrate A Learning Health System Framework into Longitudinal Population Studies to Improve Health Response in Africa. - Kadengye, Damazo T.; Kiragga, Agnes N. (Kabale University, 2024)
Longitudinal population studies (LPSs) in Africa have the potential to become powerful engines of change by adopting a learning health system (LHS) framework. This is a call-to-action opinion and highlights the importance of integrating an LHS approach into LPSs, emphasizing their transformative potential to improve population health response, drive evidence-based decision-making, and enhance community well-being. Operators of LPS platforms, community members, government officials, and funding agencies have a role to contribute to this transformative journey of driving evidence-based interventions, promoting health equity, and fostering long-term public health solutions for African communities.